The Influence of Leadership Style and Work Environment Against Work Ethic and Tutoring at PKBM in Tangerang City - Nazir, Ahmad; Widodo, Adji; Barsah, Akhmar (Jurnal Mandiri : Ilmu Pengetahuan, Seni, dan Teknologi, 2021)
The purpose of this study was to determine the influence of leadership style (X1) on work ethic (Y1), leadership style (X1) on teacher's performance (Y2), work ethic (Y1) on teacher's performance (Y2) and the Work environment (X2).) On work ethics, (Y1) Work environment (X2) on tutoring (Y2) at PKBM in Tangerang City. The method used is qualitatively descriptive with a population of 165 using a random sampling method, namely 117 samples of the existing population. Research results Statistical test on model 1 with tcount> ttable (3.404> 1.97) and Sig <0.05 (0.000 <0.05), leadership style sometimes has a positive and significant influence on work ethic. Value Fcount> Ftable (14.815> 3.06) and Sig <0.05 (0.000 <0.05), management style and work environment have a positive and significant effect on work ethic at the same time. In model 2, the value of tcount> ttable (5.555> 1.97) and Sig <0.05 (0.000 <0.05) is obtained. The leadership style has a partially positive and significant effect on the tutor's performance. With the value of tcount> ttable (3.447> 1.97) and Sig <0.05 (0.001 <0.05), the working environment has a partially positive and significant effect on the teacher's performance. The value of tcount> ttable (4.261> 1.97) and Sig <0.05 (0.000 <0.05), partly work ethic, has a positive and significant effect on the teacher's performance. The value of Fcount> Ftable (35.927> 2.67) and Sig <0.05 (0.000 <0.05), the leadership style, the work environment and the work ethic all have a positive and significant effect on the tutor's performance.